Transitioning From Bimodal to Bilateral Cochlear Implant Listening: Speech Recognition and Localization in Four Individuals. - Potts, Lisa G.; Litovsky, Ruth Y. (American Journal of Audiology, 2014)
Purpose: The use of bilateral stimulation is becoming common for cochlear implant (CI) recipients with either (a) a CI in one ear and a hearing aid (HA) in the nonimplanted ear (CI&HA--bimodal) or (b) CIs in both ears (CI&CI--bilateral). The objective of this study was to evaluate 4 individuals who transitioned from bimodal to bilateral stimulation. Method: Participants had completed a larger study of bimodal hearing and subsequently received a second CI. Test procedures from the bimodal study, including roaming speech recognition, localization, and a questionnaire (the Speech, Spatial, and Qualities of Hearing Scale; Gatehouse & Noble, 2004) were repeated after 6-7 months of bilateral CI experience. Results: Speech recognition and localization were not significantly different between bimodal and unilateral CI. In contrast, performance was significantly better with CI&CI compared with unilateral CI. Speech recognition with CI&CI was significantly better than with CI&HA for 2 of 4 participants. Localization was significantly better for all participants with CI&CI compared with CI&HA. CI&CI performance was rated as significantly better on the Speech, Spatial, and Qualities of Hearing Scale compared with CI&HA. Conclusions: There was a strong preference for CI&CI for all participants. The variability in speech recognition and localization, however, suggests that performance under these stimulus conditions is individualized. Differences in hearing and/or HA history may explain performance differences.